Distributed Method for the Backup of Massive Unstructured Data. Issue 3 (March 2021) - Duan, Junhong; Yang, Bo
Abstract: In order to solve the existing problems for the backup of massive unstructured data with its performance bottleneck of single server, in this paper we propose a distributed method for the backup of massive unstructured data. In the backup method, through using a combination of load balancing algorithm and distributed algorithm, the backup system assign task of backup to each production server. Multiple servers backup massive unstructured data stored in shared storage to the backend server. The backup system can make full use of the performance resources of servers in environment production, reduce the single server performance bottlenecks, to avoid the single server hunger, increased the speed of backup.